(untitled) (Research, Society and Development, 2022)
With the pandemic there have been major changes in all social sectors. The research is to investigate the reasons related to the increase in female entrepreneurship in the pandemic period, in particular in the food sector, in the city of Itapagipe-MG. This study aims to raise relevant facts about the spread of this enterprise. The methodology used is characterized by the qualitative approach, conducted in an exploratory way, focused on a case study, where it aims to know and analyze the subject, through the application of a questionnaire. Finally, it was possible to understand some reports about the present situation, and two possible answers to this problem were arranged: undertake by opportunity or necessity. The research showed important data, such as level of education, marital status, number of children and monthly gain of those involved. According to the analysis, it was possible to conclude that most women began to undertake for necessary.